Analisis Kewenangan Diskresi Kepolisian dalam Proses Penyidikan Perkara Tindak Pidana Pencemaran Nama Baik - Jekli Tosubu; Robby Waluyo Amu; Ibrahim Ahmad (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The implementation of police discretion in the process of investigating criminal defamation cases shows that discretion is an important instrument for police officers in assessing, determining, and following up on a criminal report based on urgency, public interest, and the principles of proportionality and professionalism. In cases of defamation, which are often subjective and private, discretion allows investigators to consider various factors such as motive, impact, and the possibility of resolution outside the criminal path. Factors Affecting the Implementation of Police Discretion in the Process of Investigating Criminal Defamation Cases show that discretion is not carried out absolutely, but is influenced by various internal and external factors, namely: Legal and Regulatory Aspects, Case Characteristics, Professionalism and Ethics of Investigators, Social and Environmental Pressure, Facilities and Resources. Police Discretion should be regulated more clearly in positive law other than Law Number 2 of 2002 and the Criminal Procedure Code so that the principles of Legal Certainty and Respect for Human Rights are more apparent. Police offices need to provide special facilities such as mediation rooms that are neutral, comfortable, and support the creation of a dialogical atmosphere between the disputing parties. Increasing the number of investigators and managing a more balanced workload will provide space for investigators to consider the discretionary path more seriously without sacrificing work efficiency. The Standard Operating Procedure (SOP) for discretion at the Polres level needs to be adjusted to local socio-cultural characteristics. In Gorontalo, for example, a legal approach that is sensitive to family values and customs must be officially accommodated in work procedures.